1953
DOI: 10.1017/s0022172400015795
|View full text |Cite
|
Sign up to set email alerts
|

Studies on respiratory infection: I. The influence of particle size on respiratory infection with anthrax spores

Abstract: Experiments to determine the role of particle size in the infectivity of anthrax spores are described. Clouds of homogeneous particles were produced. The mortality-dosage curves for guinea-pigs and monkeys are given for clouds of various particle sizes. Data are given on the effect of time in the concentration-time relationship. The results are compared with those recorded by other workers on the relationship of particle size to respiratory retention.Infectivity was highest with single-spore clouds, falling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
157
6
2

Year Published

1956
1956
2006
2006

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(169 citation statements)
references
References 7 publications
4
157
6
2
Order By: Relevance
“…Then, the probability that at least one spore germinates, the attack rate, is p ϭ 1 Ϫ exp(ϪD ͞( ϩ )). This exponential functional form for the attack rate is consistent with empirical data from animal studies in the experimental dose ranges studied (9)(10)(11)(12)(13)(14).…”
Section: Competing-risks Modelsupporting
confidence: 81%
“…Then, the probability that at least one spore germinates, the attack rate, is p ϭ 1 Ϫ exp(ϪD ͞( ϩ )). This exponential functional form for the attack rate is consistent with empirical data from animal studies in the experimental dose ranges studied (9)(10)(11)(12)(13)(14).…”
Section: Competing-risks Modelsupporting
confidence: 81%
“…The influence of aerosol particle size on respiratory infection due to the inhalation of anthrax spores was described in a previous paper (Druett, Henderson, Packman & Peacock, 1953). It was shown that the number of spores necessary to cause infection rose sharply with particle size, and was also related to the fact that the majority of larger-sized particles are deposited in the upper respiratory tract.…”
Section: Introductionmentioning
confidence: 89%
“…A highly virulent strain of Bacillus anthracis was used. Its origin and infectivity, and the method of production of the spore suspensions used for cloud production, have been described (Druett, Henderson, Packman & Peacock, 1953).…”
Section: Methodsmentioning
confidence: 99%